2024
DOI: 10.5477/cis/reis.144.139
|View full text |Cite
|
Sign up to set email alerts
|

Mayores que viven solos: una panorámica a partir de los censos de 1991 y 2001

Abstract: Cambio demográfi co • Características demográfi cas • Censo • Europa • Personas mayores • Formas de convivencia Resumen El artículo analiza la evolución de la vida en solitario de las personas de 65 a 84 años no casadas y que no cohabitan en pareja entre 1991 y 2001 en siete países europeos (España, Francia, Grecia, Hungría, Portugal, Rumanía y Suiza). Para ello se utilizan microdatos censales procedentes de IPUMS (Integrated Public Use Microdata Series). Se examina el papel de cinco variables en la probabilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Although the grouping of countries into distinct categories is far from perfect, the data from the 2011 round of European population censuses confirm the existence of this rather robust family continuum: where the strength of family ties, networks and practices is greater, the proportion of elderly women living alone tends to be lower. As a previous study (Zueras and Miret 2013 ) has shown, in Europe the country differences in the propensity of older people to live alone persist even after controlling for several structural variables (gender, age, marital status, level of education, and employment status) and they mirror the North/South familistic axis.…”
Section: Living Arrangements Of Older Women In Spainmentioning
confidence: 64%
See 2 more Smart Citations
“…Although the grouping of countries into distinct categories is far from perfect, the data from the 2011 round of European population censuses confirm the existence of this rather robust family continuum: where the strength of family ties, networks and practices is greater, the proportion of elderly women living alone tends to be lower. As a previous study (Zueras and Miret 2013 ) has shown, in Europe the country differences in the propensity of older people to live alone persist even after controlling for several structural variables (gender, age, marital status, level of education, and employment status) and they mirror the North/South familistic axis.…”
Section: Living Arrangements Of Older Women In Spainmentioning
confidence: 64%
“…The Spanish case is very clear on this point. Despite being a society with strong family ties and kinship networks, living alone has risen substantially among all subpopulations, including older women (Requena 2004 ; Zueras and Miret 2013 ). As given in Table 1 , over the past three decades single living has been steadily increasing among women 65+.…”
Section: Living Arrangements Of Older Women In Spainmentioning
confidence: 99%
See 1 more Smart Citation
“…Some U.S. studies have found that the higher a person's level of education, the more likely they are to live alone as an older adult (Festy & Rychtarikova, 2008;Palloni, 2001;Zueras & Gamundi, 2013). Others concluded that higher education is associated with better health and having fewer offspring; therefore, these seniors were less likely to live with one of their older children (Zueras & Gamundi, 2013). Meanwhile, global data collected by the United Nations (2005) found no relationship between education and living alone.…”
Section: Introductionmentioning
confidence: 99%
“…En este contexto de análisis nos encontramos con numerosos trabajos de investigación que han destacado la existencia de un modelo de familia mediterránea caracterizado, entre otros factores, por la solidaridad intergeneracional y por la moderada incidencia de los hogares multigeneracionales en comparación con otros países europeos (Carrascosa y Sancho, 2013;Naldini, 2003, Iacovou y Skew, 2011Eurofound, 2014;Zueras y Miret, 2013). Si bien los estudios sugieren que el fenómeno de los hogares multigeneracionales es más frecuente en los países del sur de Europa que en el norte de Europa (Koslowski, 2009;Tomassini et al, 2004), son más bien escasos los estudios disponibles que analicen la relación entre las prácticas de solidaridad intergeneracional en las familias extensas y el bienestar de las personas que residen en este tipo de hogares (Albuquerque, 2011;Hank y Buber, 2009;Koslowski, 2009).…”
unclassified